Association of Maghreb countries with the European Union and entry of FDI - Nasri, Leila (Journal of Ecohumanism, 2025)
The objective of this paper is to analyze the effect of the Free Trade Agreement (FTA) on the attractiveness of FDI in three countries of the Arab Maghreb Union (Algeria, Morocco and Tunisia) for the period 1987-2022. We used a Tobit model to distinguish the FDI created by this agreement from those that created by other factors.